THE EFFECTS OF SELF HYPNOSIS TECHNIQUE TOWARDS THE DECREASING OF MENSTRUATION PAIN LEVEL TO GIRLS TEENAGER AT SMKN 2 SUMEDANG OF SUMEDANG REGENCY IN 2019 - Wulan Nur Insani (Jurnal Ilmiah Bidan (JIB), 2020)
Dysmenorrhea or menstrual cramps can be experienced by more than a half women who are having menstruation and the prevalence are so variated. Based on the data from various countries, the number of dysmenorhea cases in the world are quite high. It is approximately 50% from all women in the world have 12% of serious menstruation pain, 37% of medium menstruation pain and 49% of mild menstruation pain. Based on the research results by Lisnawati Mela stated that most of the girls students at SMAN 3 Sumedang had mild menstruation pain and some of them had medium menstruation pain. The effects of dysmenorrhea experienced by girls teenager one of them is disturbing learning activities at school. Based on the previous survey find out that the effects of dysmenorrhea at SMKN 2 Sumedang gain results that (73%, 3%) of girls teenager were able to do school lessons as usual but the menstruation pain can disturb the learning consentration, (26,7%) of girls teenager stayed in The Health School Unit Room and did not able to do school lessons as usual. One of the ways to solve the problem that is by self hypnosis or relaxation technique. The aims of this research are to know the effects of self hypnosis research towards the decreasing of menstruation pain at SMKN 2 Sumedang in 2019. The research design used pre experimental design with One Group Pre Test – Posttest Instrument research used Numerical Rating Scale (NRS) paper, univariate data analysis and bivariate analysis with t-test. The univariate results find out that the menstruation pain scale to girls teenager before did self hypnosis most of them were in scale of 5 with 54 girls teenager students (37%) , while the menstruation pain after had given self hypnosis to the first month that most of them in the pain scale of 3 as many as 47 girls teenager (32,6%) in the second month most of the girls teenager had pain scale of 2 as many as 55 girls teenager (38.2%) and in the third month most of the girls teenager had pain menstruation in the scale of 1 were as many as 66 girls teenager (45,8%). Bivariate data analysis results used t-test find out that the p value < α ( p value = 0,000).